Pengaruh Komitmen Dan Kedisiplinan Kerja Terhadap Kinerja Pegawai Pada Puskesmas Kecamatan Tompobulu Kabupaten Maros - Taufik, Ansar; Riskiani; Irwan, Andi (Jurnal Online Manajemen ELPEI, 2024)
The analytical method used in this research is quantitative descriptive to answer the hypothesis in this research. In answering the hypothesis, the descriptive method is used, the instrument test consists of validity and reliability tests, the classical assumption test consists of normality, multicollinearity and heteroscedasticity tests, the regression test consists of multiple linear regression analysis, correlation and determination coefficients and the hypothesis test consists of partial and partial tests. simultaneously. The results of the research are (1) The work commitment variable on employee performance is positive. This illustrates that if there is an increase in employee work ability by 1%, it will affect employee performance by 29.1%, reinforced by hypothesis testing. then the conclusion is that hypothesis X 1 is accepted or proven to have a significant effect. (2) Discipline has a positive effect on employee performance. This means that every time there is an increase in the level of employee discipline by 1%, it will affect the level of employee performance by 22.2% which is confirmed by the results of hypothesis testing, namely tcount 2.253 > ttable 1.98827 which means that the accepted hypothesis is accepted. Meanwhile, the significance value shows 0.027 > SIg 0.05 with the conclusion that hypothesis X2 in this study is accepted or proven to have a significant effect. Meanwhile, testing the third hypothesis, namely the calculated F value of 9.036 > F table 3, 11 and a sig value of 0.0 00, the conclusion is that the hypothesis is proven that work commitment and work discipline have a significant effect on employee performance.